Representation of low and middle income countries in traumatic stress journals from 2006 to 2015. (December 2019) - Robson, Brian; Chang, Leanne; Kaminer, Debra
Although the majority of trauma survivors reside in low and middle income countries, these regions have historically been poorly represented in traumatic stress research. However, a recent review of geographic representation within traumatic stress journals is lacking. This study reviewed all articles published between 2006 and 2015 in six leading traumatic stress journals. When articles ( n  = 2530) were categorised by region, less than one tenth (9.76%; n  = 247) were representative of low and middle income countries. All articles categorised as being from a low and middle income country were then coded for the regional and country representations of samples, author affiliations, and funding sources, and for type of research methodology. The majority of primary author teams (56.28%) and funding sources (55.87%) for articles based in low and middle income countries were located in high-income countries. The majority of low and middle income country articles (71.66%) used structured symptom questionnaires of which more than two thirds (70.6%) assessed symptoms of posttraumatic stress disorder. These findings indicate that knowledge production about traumatic stress in domain-specific journals reflects a state of ongoing geographic inequality and that research published from low and middle income countries reflects predominantly etic methodologies centred on measuring posttraumatic stress disorder. The implications are discussed and recommendations are offered for developing a research base in domain-specific journals that better represents the experiences and needs of trauma survivors in low and middle income countries.